A FATWA ISSUED BY THE COUNCIL OF INDONESIAN ULAMA (MUI) AGAINST THE U.S. INVASION TO IRAQ - Yanwar Pribadi (Al Qalam, 2009)
The Council of Indonesian Ulama (the MUI) issued a fatwa number 2 year of 2003 entitled Penyerangan Amerika Serikat dan Sekutunya terhadap Irak (the U.S and its allies aggression to Iraq). The fatwa was issued following the U.S. invasion to Iraq and because of several reasons, mainly after numerous demonstrations in several areas of Indonesia.The fatwa is mainly about the MUI's attitude concerning the invasion of the U.S. to Iraq. This paper will describe three main themes; firstly, the study will define the, existence of the fatwa, including the backgrounds of the issuance of the fatwa. Secondly, it will attempt to examine the responses of Indonesian scholars and ulama' toward the invasion. Thirdly, it will compare other fatwas from other countries, including, similar and different fatwas.